Effect of Structured Nursing Intervention on Knowledge and Treatment Adherance Among Patients With End Stage Renal Disease in Kano Metropolis - Aikawa, Hussaini Muhammad; Kombo, Salihu Abdulrahman Abdulrahman; Sani, Dalhat Khalid; Dalhatu, Adamu; Sani, Sani Mohammed; Abdurrashid, Idris (Universitas Fort De Kock Bukittinggi, 2024)
Background: Chronic Renal Failure is a progressive irreversible deterioration in renal function in which the body’s power to maintain metabolic, fluid, and electrolyte balance fails, resulting in uremia which contributes to the patient's dependence upon hemodialysis for the maintenance of the internal milieu and to avoid uremia. Patients with end-stage renal disease (ESRD) are characterized by low levels of physical activity and a continuous decline in physical function. The main aim of the study was to assess the effect of structured nursing intervention on treatment adherence among patients with end-stage renal disease in Kano Metropolis. Methods: This study utilized a two-group pretest-post-test quasi-experimental design. Patients receiving dialysis care at Muhammadu Abdullahi Wase Teaching Hospital and Abubakar Imam Urology Hospital were purposively selected as experimental and control groups respectively. A total of 422 participants were estimated and selected for the study and equally shared among the two groups, i.e. 211 for the control and 211 for the experimental group. All statistical data were analyzed and described using simple frequencies, Chi-square, T-test and regressions. Results: Regarding treatment adherence, the pre-intervention mean score was 52.9 and 50.00, and the post-intervention score was 73.2 and 54.6 in the intervention and control groups, respectively. The effectiveness of the intervention was tested using unpaired t-test which was found to be significantly effective (p<0.005). Conclusion: Based on the findings of the study, the structured nursing intervention was effective in improving the level of knowledge regarding the disease and treatment adherence (p<0.005) among patients with end-stage renal disease in the Kano metropolis. It is therefore recommended that the nephrology nurses, hospital administrators, and the general public join hands to make the services accessible and affordable to these patients to maintain their normal life activities through good adherence to the treatment regimen.